Ammonia activation using a heteroleptic stannylene and lithium stannylenoid formation facilitated by hemilabile iminophosphorane-based ligands - Krengel, David M.J.; Graw, Nico; Herbst-Irmer, Regine; Stalke, Dietmar; Townrow, Oliver; Fischer, Malte (Inorganic Chemistry Frontiers, 2024)
Heteroleptic stannylenes, featuring pendant hemilabile iminophosphorane functionalities and kinetically stabilizing terphenyl ligands, were synthesized straightforwardly through formal C-H activation. Subsequently, they were investigated for their ability to activate ammonia through N-H bond scission. By combining synthetic modifications of the ancillary ligand framework and computational analyses, detailed insights into the mechanism of NH3 activation by these systems were obtained, highlighting an activation pathway at tin without a change in oxidation state. Additionally, an observed by-product during these studies underscores the non-innocence of a lithium salt in the synthesis of the stannylene starting materials, providing access to a novel lithium stannylenoid.
CRIS-Team Scopus Importer:2024-10-25

A Rare Case of Magnesium Alkyl Mediated CO-to-Alkoxide Conversion - Townrow, Oliver; Richter, Tim; Langer, Jens; Harder, Sjoerd (Chemistry - A European Journal, 2024)
Alcohols can be produced by nucleophilic addition at the C=O functional group of ketones or aldehydes. Such C−C bond formations generally proceed smoothly and selective. In contrast, nucleophilic addition at carbon monoxide is considerably more complex and unselective due to the instability of polar metal acyl intermediates. Herein, we report a magnesium alkyl complex, stabilised with a dipyrromethenide ligand, and its reactivity with CO2 and CO. Whilst the reaction with CO2 gave the expected carboxylate, reaction with CO took a surprising course, resulting in an alkoxide by formation of three new C−C bonds in a single reaction. An intertwined experimental and computational approach sheds light on the unusual reactivity of a carbene intermediate.
CRIS-Team Scopus Importer:2024-11-29
Keywords: carbon monoxide; C−H activation; dipyrromethane; magnesium; metal alkyl

Dipyrromethene as a Ligand for the Stabilization of Low-Valent Gallium Complexes - Richter, Tim; Thum, Stefan; Vilpas, Timothy; Townrow, Oliver; Klerner, Lukas; Langer, Jens; Harder, Sjoerd (Organometallics, 2024)
We investigated the low-valent chemistry of Al and Ga with the ligand tBuDPM, a dipyrromethene ligand scaffold with two large tBu groups in the flanking 1- and 9-positions and a mesityl group in the backbone 5-position. Attempted synthesis of (tBuDPM)AlI by reduction of (tBuDPM)AlI2 with KC8 failed. However, reduction of (tBuDPM)GaI2 (1) with K/KI led to successful isolation of (tBuDPM)GaI (3). The GaII intermediate in the reduction process crystallized as a digallane: [(tBuDPM)GaI]2 (2). Also, 3 crystallized as a dinuclear complex with a Ga-Ga bond. However, in a benzene solution, the 3 dissociates into two mononuclear complexes. Reaction of a benzene solution of (tBuDPM)GaI with excess Me3SiN3 gave the tetrazagallole product (tBuDPM)Ga[N4(SiMe3)2] (4) and not the alternative azide-amide product (tBuDPM)Ga(N3)[N(SiMe3)2], which according to calculations is thermodynamically considerably more stable. Theoretical investigations on the nature of the Ga-Ga bonds in 2 and 3 and the mechanism for selective formation of 4 have been included.
CRIS-Team Scopus Importer:2024-06-28

En Route to a Molecular Terminal Tin Oxide - Kreßner, Leon; Duvinage, Daniel; Puylaert, Pim; Graw, Nico; Herbst-Irmer, Regine; Stalke, Dietmar; Townrow, Oliver; Fischer, Malte (Inorganic Chemistry, 2024)
In the pursuit of terminal tin chalcogenides, heteroleptic stannylenes bearing terphenyl- and hexamethyldisilazide ligands were reacted with carbodiimides to yield the respective guanidinato complexes. Further supported by quantum chemical calculations, this revealed that the iso-propyl-substituted derivative provides the maximum steric protection achievable. Oxidation with elemental selenium produced monomeric terminal tin selenides with four-coordinate tin centers. In reactions with N2O as oxygen transfer reagent, silyl migration toward putative terminal tin oxide intermediates gave rise to tin complexes with terminal ─OSiMe3 functionality. To prevent silyl migration, the silyl groups were substituted with cyclohexyl moieties. This analogue exhibited distinctively different reactivities toward selenium and N2O, yielding a 1,2,3,4,5-tetraselenastannolane and chalcogenide-bridged dimeric compounds, respectively.
CRIS-Team Scopus Importer:2024-04-19

Metal Vapour Synthesis of an Organometallic Barium(0) Synthon - Townrow, Oliver; Färber, Christian; Zenneck, Ulrich; Harder, Sjoerd (Angewandte Chemie International Edition, 2023)
A hydrocarbon-soluble barium anthracene complex was prepared by means of metal vapour synthesis. Reaction of 9,10-bis(trimethylsilyl)anthracene (Anth′′) with barium vapour gave deep purple Ba(Anth′′) which after extraction with diethyl ether crystallised as the cyclic octamer [Ba(Anth′′)⋅Et2O]8. Dissolution in benzene or toluene led to replacement of the Et2O ligand with a softer arene ligand and isolation of Ba(Anth′′)⋅arene. Diffusion ordered spectroscopy (DOSY NMR) measurements in benzene-d6 indicate solution species with a molecular weight that equals a trimeric constitution. Natural population analysis (NPA) assigned charges of +1.70 and −1.70 to Ba and Anth′′, respectively, relating to highly ionic Ba2+/Anth′′2− bonding. Preliminary reactivity studies with air, Ph2C=NPh, or H2 show that the complex reacts as a Ba0 synthon by release of neutral Anth′′. This soluble molecular Ba0/BaII redox synthon provides new routes for the syntheses of barium complexes under mild conditions.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Barium; Cyclic Organometallics; Low-Valent; Metal Vapour Synthesis; Reducing Agents

Selectivity control in the reactivity of dipyrromethene gallium(I) complexes - Richter, Tim; Thum, Stefan; Townrow, Oliver; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Journal of Organometallic Chemistry, 2024)
Following the recent isolation and structural characterization of the first low-valent GaI complex with a monoanionic dipyrromethenide ligand (DPM), herein (DPM)GaI complexes with bulky aryl-substituents in the 1- and 9-positions are described. This study focusses on three DPM ligands with mesityl substituents (MesDPM), 2,6-diisopropylphenyl substituents (DIPPDPM), or 10-isopropyl-9-anthracenyl substituents (iPr-AnthDPM); the synthesis to the latter unknown ligand is described. The precursors (RDPM)GaI2 were obtained by reaction of the corresponding alkali metal complexes (RDPM)M (M = Na or K) with GaI3 and characterized by X-ray diffraction. Crystal structures show the efficient shielding of the GaI2 unit by two flanking aryl groups. In a subsequent reduction step, (DIPPDPM)GaI and (iPr-AnthDPM)GaI have been isolated. Comparison of the crystal structure of (DIPPDPM)GaI with that of a similar β-diketiminate GaI complex shows that the Ga center in the DPM complex is well shielded by flanking DIPP substituents. Despite this favorable ligand geometry, isolation of the corresponding (DPM)Ga=N(SiMe3) complexes failed due to further reaction with a second equivalent of Me3SiN3. This resulted in clean formation of the tetrazagallole complex (tBuDPM)Ga[N4(SiMe3)2] and the amide/azide combination (iPr-AnthDPM)Ga(N3)N(SiMe3)2, both structurally characterized by X-ray diffraction. Selective formation of both complexes shows that the substituents in the DPM ligand effectively control the course of the reaction. DFT calculations show that independent of the substituent (tBu, DIPP, or iPr-Anth) the amide/azide combination is always circa 20 kcal/mol more stable than the tetrazagallole product. The latter must therefore be formed by kinetic control.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Azide; Dipyrromethene ligand; Gallium; Imido; Low-valent

Synthesis, Structure, and Reactivity of a Superbulky low-Valent β-diketiminate Ga(I) Complex - Richter, Tim; Thum, Stefan; Townrow, Oliver; Wiesinger, Michael; Langer, Jens; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2024)
A low-valent GaI complex with the superbulky β-diketiminate ligand DIPePBDI (HC[C(Me)N−DIPeP]2, DIPeP=2,6-C(H)Et2-phenyl)) was obtained by reduction of (DIPePBDI)GaI2 (1) with KC8 in toluene. Considering that (BDI)GaI and analogue (BDI)AlI complexes are prone to decomposition and can generally only be obtained in low yields (20–40 %), the quantitative formation of (DIPePBDI)GaI (2) is remarkable and no doubt related to its excellent thermal stability even in refluxing toluene. Although the low-valent metal center in 2 is sterically protected by the superbulky DIPePBDI ligand, it is readily oxidized by N2O to give intermediate (DIPePBDI)Ga=O which readily decomposed by abstracting a proton from the backbone Me-substituent. Reaction with trimethylsilyl azide gave an intermediate imido complex (DIPePBDI)Ga=N(SiMe3)2 which reacted with a second equivalent of Me3SiN3 to a mixture of an azide/amido complex (DIPePBDI)GaN3[N(SiMe3)2] (4) and a tetrazagallole complex (DIPePBDI)Ga[N4(SiMe3)2] (5) in a 1 : 2 ratio. Whereas the azide/amido complex 4 could be structurally characterised, the tetraazagallole complex 5 was identified by NMR spectroscopy. DFT calculations on (DIPePBDI)GaI (2) and its reaction products complement this study.
CRIS-Team Scopus Importer:2024-06-07
Keywords: bulky; Gallium; Low-valent; β-diketiminate

Tuning the selectivity of P4 reduction at alkaline-earth metal centres - Thum, Stefan; Townrow, Oliver; Langer, Jens; Harder, Sjoerd (Chemical Science, 2025)
Reduction of P4 with β-diketiminate MgI complexes, (BDI)MgMg(BDI), depends strongly on the bulk of the ligand. Whereas superbulky BDI ligands gave selective reduction to P42− in a butterfly conformation, reduction with a less bulky ligand gave various products among which P84− had a realgar-type structure. The selectivity of P4 reduction can also be controlled by metal choice. Reduction of P4 with CaI synthons of general type (BDI*)Ca-X-Ca(BDI*) in which BDI* is a superbulky ligand and X is a bridging dianion (C6H62− < p-xylene2− < N22−) led to reduction of P4 to the very common, stable Zintl anion P73−. Monitoring this process with 31P NMR shows that cyclo-P42− is an intermediate en route to P73−. Conversion rates increase with increasing reducing power: X = C6H62− < p-xylene2− < N22−. A complex with the weakly reducing DBA2− dianion led to selective P4 reduction to cyclo-P42− (DBA = 9,10-dimethyl-diboraanthracene). DBA inhibits P4-to-P7 conversion, most likely by capturing the electron needed for further P4 reduction by radical processes. Experimental investigations are supported by crystal structure determinations and a computational DFT study which also shows that the nature of metal-P4 bonding (covalent or ionic) determines the preference for formation of butterfly-shaped P42− or planar 6π-electron aromatic cyclo-P42−
CRIS-Team Scopus Importer:2025-02-17